3D in-situ hollow carbon fiber/carbon nanosheet/Fe3C@Fe3O4 by solventless one-step synthesis and its superior supercapacitor performance. (20th October 2017) - Ju, Jaechul; Kim, Minjae; Jang, Seokhoon; Kim, Yeongseon; Choi, Yongheum; Baeck, Sung-Hyeon; Shim, Sang Eun
Graphical abstract: Highlights: 3D in-situ h-CNF/CNS/Fe3 C@Fe3 O4 was constructed using ferrocene and oleic acid by a solventless one-step process. h-CNF/CNS/Fe3 C@Fe3 O4 exhibited higher specific capacitance of 327 F g −1 at 5 mV s −1 and 210 F g −1 at 10 mV s −1, and superior retention of 108% after 6000 cycles at 100 mV s −1 . Carbon nanoshell comprising h-CNF and CNS well encapsulates Fe3 C@Fe3 O4 core materials and this sturdy structure endows high cycle stability up to 6000 cycles. Abstract: Herein, 3D in-situ hollow carbon fiber/carbon nanosheet/Fe3 C@Fe3 O4 (h-CNF/CNS/Fe3 C@Fe3 O4 ) was constructed using ferrocene and oleic acid by a solventless one-step process that did not require additional filtering, neutralization, drying, or calcination steps. The iron-oleate chelating structure that self-assembled during annealing facilitated the fabrication of 3D in-situ h-CNF/CNS/Fe3 C@Fe3 O4 by undergoing graphitization at 600 °C. This carbon shell of the 3D in-situ h-CNF/CNS/Fe3 C@Fe3 O4 was derived from the two cyclopentadienyl rings in ferrocene. This hybrid material made from economically cheap oleic acid exhibited superior supercapacitive behavior: high specific capacitance of 327 F g −1 at 5 mV s −1 and 210 F g −1 at 10 mV s −1, good rate capability of 60 F g −1 at 10 A g −1 (compared to 70 F g −1 at 1 A g −1 for pure Fe3 O4 ), and superior retention of 108% after 6000 cycles at 100 mV s −1 . These superior supercapacitive properties were ascribed to the 3D graphitic h-CNF/CNS for enhancing electrical conductivity and the carbonaceous shell over Fe3 C@Fe3 O4 core for buffering the bulk expansion of iron-related particles.